Communication failures in patient sign-out and suggestions for improvement: a critical incident analysis. Issue 6 (2nd December 2005) - Arora, V; Johnson, J; Lovinger, D; Humphrey, H J; Meltzer, D O
Abstract : Background: The transfer of care for hospitalized patients between inpatient physicians is routinely mediated through written and verbal communication or "sign-out". This study aims to describe how communication failures during this process can lead to patient harm. Methods: In interviews employing critical incident technique, first year resident physicians (interns) described (1) any adverse events or near misses due to suboptimal preceding patient sign-out; (2) the worst event due to suboptimal sign-out in which they were involved; and (3) suggestions to improve sign-out. All data were analyzed and categorized using the constant comparative method with independent review by three researchers. Results: Twenty six interns caring for 82 patients were interviewed after receiving sign-out from another intern. Twenty five discrete incidents, all the result of communication failures during the preceding patient sign-out, and 21 worst events were described. Inter-rater agreement for categorization was high (κ 0.78–1.00). Omitted content (such as medications, active problems, pending tests) or failure-prone communication processes (such as lack of face-to-face discussion) emerged as major categories of failed communication. In nearly all cases these failures led to uncertainty during decisions on patient care. Uncertainty may result in inefficient or suboptimal care such as repeat or unnecessary tests. Interns desired thorough but relevant face-to-face verbal sign-outs that reviewed anticipated issues. They preferred legible, accurate, updated, written sign-out sheets that included standard patient content such as code status or active and anticipated medical problems. Conclusion: Communication failures during sign-out often lead to uncertainty in decisions on patient care. These may result in inefficient or suboptimal care leading to patient harm.